Skeletal muscle mitochondrial dysfunction is associated with increased Gdf15 expression and circulating GDF15 levels in aged mice - J. Chen; J. Kastroll; F. M. Bello; M. M. Pangburn; A. Murali; P. M. Smith; K. Rychcik; K. E. Loughridge; A. M. Vandevender; N. Dedousis; I. J. Sipula; J. K. Alder; et al. (Scientific Reports)
Abstract Growth differentiation factor-15 (GDF15) is a biomarker of multiple disease states and circulating GDF15 levels are increased during aging in both pre-clinical animal models and human studies. Accordingly, multiple stressors have been identified, including mitochondrial dysfunction, that lead to induction of Gdf15 expression downstream of the integrated stress response (ISR). For some disease states, the source of increased circulating GDF15 is evident based on the specific pathology. Aging, however, presents a less tractable system for understanding the source of increased plasma GDF15 levels in that cellular dysfunction with aging can be pleiotropic and heterogeneous. To better understand which organ or organs contribute to increased circulating GDF15 levels with age, and whether changes in metabolic and mitochondrial dysfunction were associated with these potential changes, we compared young 12-week-old and middle-aged 52-week-old C57BL/6 J mice using a series of metabolic phenotyping studies and by comparing circulating levels of GDF15 and tissue-specific patterns of Gdf15 expression. Overall, we found that Gdf15 expression was increased in skeletal muscle but not liver, white or brown adipose tissue, kidney or heart of middle-aged mice, and that insulin sensitivity and mitochondrial respiratory capacity were impaired in middle-aged mice. These data suggest that early changes in skeletal muscle mitochondrial function and metabolism contribute to increased circulating GDF15 levels observed during aging.